2009
DOI: 10.1093/ndt/gfp611
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular and proximal tubule cysts as early manifestations of Pkd1 deletion

Abstract: These studies indicate that Pkd1 deletion is associated with a massive loss of solutes (from E13.5) and increased cAMP levels (E14.5) associated with polyhydramnios. These abnormalities precede renal cysts (E15.5), first derived from glomeruli and proximal tubules and later from the collecting ducts, reflecting the expression pattern of Pkd1 in maturing epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 28 publications
5
24
1
Order By: Relevance
“…This is consistent with PT cysts predominating in early-onset ADPKD cases, with a similar shift from PT to CD cysts associated with completion of kidney development in ARPKD (28,29,39,76,77). The observation that the majority of adult cysts are of CD origin correlates with the AVPR2 antagonists showing some benefit in ADPKD (31,32,78).…”
Section: Figuresupporting
confidence: 68%
“…This is consistent with PT cysts predominating in early-onset ADPKD cases, with a similar shift from PT to CD cysts associated with completion of kidney development in ARPKD (28,29,39,76,77). The observation that the majority of adult cysts are of CD origin correlates with the AVPR2 antagonists showing some benefit in ADPKD (31,32,78).…”
Section: Figuresupporting
confidence: 68%
“…Of interest, Pkd1 mouse models also show heterogeneity in the segments affected. 25,26 Although ANKS6 rat and mouse mutations are located in the same SAM domain and are physically close, they might induce different conformational changes in the rat and the mouse, which would alter different ANKS6 functions, and/or disrupt interactions with different protein partners. This hypothesis is supported by the replacement of a hydrophilic (arginine) by a hydrophobic (tryptophan) amino acid in cy/+ rat and of a hydrophobic (isoleucine) by a hydrophilic (asparagine) amino acid substitution in ANKS6 I747N mouse.…”
Section: Discussionmentioning
confidence: 99%
“…PC1 regulates terminal differentiation of tubular structures in kidney and liver (2)(3)(4), as well as maintaining the structural integrity of the kidney (5) and vasculature (6). Expression studies in human and mouse showed spatiotemporal regulated expression for PC1/Pc1 (7)(8)(9)(10).…”
mentioning
confidence: 99%